Price, Customer Experience, and Customer Satisfaction and Its Influence on Customer Loyalty at Yon’s Body Repair, Kediri - Elsania, Niken; Sumantri, Bambang Agus (Universitas Nusantara PGRI Kediri, 2024)
Research aim: This study has the objective of how the influence of price, customer experience, and customer satisfaction on customer loyalty at Yon’s Body Repair Kediri. Design/Methode/Approach: In taking this sample using the technique of total sample by using a causal quantitative approach and calculation based on the Cochran formula that sample of 70 respondents was taken. This Study makes use of Google Forms and questionnaire paper which has been tested for its validity and reliability to distribute questionnaires for data collection. The data analysis technique employed in the research involved using the SPSS version 23 program to test hypotheses and calculate the coefficient of determination. Research Finding: The obtained results demonstrate that price, customer experience, and customer satisfaction all exert a significant positive influence on customer loyalty at Yon's Body Repair. It is hoped that this research, will make customers feel loyal in using it and the company can also improve its competitiveness. Theoretical contribution/Originality: Simultaneous measurement of price, customer experience, customer satisfaction variables on customer loyalty Practitioner/Policy implication: It is anticipated that readers will gain a deeper understanding of how price, customer experience, and customer satisfaction impact customer loyalty, ultimately enhancing the business's competitive edge. Research limitation: This research only focuses on the variables price, customer experience, customer experience, and customer satisfaction regarding customer loyalty.